Improving the Mathematics Learning Process of Junior High School Students in Pekanbaru with the Application of the Talking Stick Type Cooperative Learning Model - Safitri Ramadani; Alzaber (Mathematics Research and Education Journal, 2022)
Research applying the talking stick cooperative learning model aims to improve the learning process and student learning outcomes in mathematics. The research subjects were students of SMPN 26 Pekanbaru, totaling 40 students. This research is a Classroom Action Research (CAR) with two cycles. The data collection instruments consisted of observation sheets, questionnaire sheets, and learning outcomes test sheets. The data analysis technique used in this research is descriptive data analysis with observation sheets, questionnaire sheets, and analysis of learning outcomes. The results of teacher activities and student activities at each meeting showed an increase in the mathematics learning process of SMPN 26 Pekanbaru students starting from the first meeting in the first cycle to the last meeting in the second cycle. This can be seen from the number of students who completed the primary score, namely 14 students from 40 students or 35%, increasing on the first daily test to 22 students from 40 or 55%. Student learning outcomes after the learning process in the second cycle increased to 33 students or 83% in the second daily test.